South Asia's turn policies to boost competitiveness and create the next export powerhouse - López Acevedo, Gladys; Medvedev, Denis; Palmade, Vincent (South Asia development matters, 2017)
South Asia has a huge need to create more and better jobs for a growing population, especially in the manufacturing industries where it is underperforming as compared to East Asia. The report examines three critical and relatively understudied drivers of competitiveness: economies of agglomeration: firms and workers accrue benefits from locating close together in cities or clusters through urbanization and localization ; participation in global value chains: stronger competitive pressures weed out least productive firms while others improve by gaining access to new knowledge and better inputs ; firm capabilities: in order to operate close to what would be considered optimum efficiency levels given the prevailing factor prices and thus employ South Asia's abundant labor. The report shows that South Asia has great untapped competitiveness potential. Realizing this potential would require the governments in the region to pursue second generation trade policy reforms for firms to better contribute to and benefit from global value chains (e.g. facilitating imports for exporters), to facilitate the development of industrial clusters in secondary cities (cheaper and less congested than the metros) as well as to deploy policies to improve the capabilities of firms